2001
DOI: 10.1046/j.1467-2960.2001.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Active habitat selection by pre‐settlement reef fishes

Abstract: Our understanding of habitat selection by reef fish larvae has changed dramatically in the last 10 years. Fish larvae have long been considered passive particles at the mercy of ocean currents, tides and weather events. For reef fishes, ecological evidence has shown that passive dispersal alone often cannot explain larval distributions, suggesting active behaviour by reef fish larvae. While behaviourally modified passive transport may be important, recent work demonstrates that some reef fish larvae have the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 141 publications
(265 reference statements)
4
106
0
2
Order By: Relevance
“…These methods have shown that fish larvae orient and that cues such as sound and chemical plumes originating from reefs can be detected and might be used for navigation. These findings were consistent among the studies and were the subject of recent reviews (e.g., Montgomery et al 2001Montgomery et al , 2006Kingsford et al 2002;Leis 2006). However, the scope of these results is limited due to methodological constraints, as detailed below.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…These methods have shown that fish larvae orient and that cues such as sound and chemical plumes originating from reefs can be detected and might be used for navigation. These findings were consistent among the studies and were the subject of recent reviews (e.g., Montgomery et al 2001Montgomery et al , 2006Kingsford et al 2002;Leis 2006). However, the scope of these results is limited due to methodological constraints, as detailed below.…”
Section: Introductionsupporting
confidence: 83%
“…However, fish are known to develop swimming capacities early (Leis 2006); hence, orientation of young individuals is potentially influential to the connectivity between adult populations. The behavior of younger larvae in the pelagic environment is still completely unknown and may involve other cues, such as magnetic or electric fields, sun position, swell, and waves (Montgomery et al 2001). Current methods are not appropriate to tackle these questions.…”
Section: Detection and Quantification Of Marine Larvae Orientation Inmentioning
confidence: 99%
“…The presence of settlement-size permit in windward beach samples and the lack of similar-size individuals in other habitats suggest that permit are actively settling along beaches. Such active settlement should not be surprising since larvae can use olfaction and sound to select settlement habitats (reviewed in Montgomery et al 2001). Although such cues were not examined in this study, if observed juvenile abundance patterns resulted from non-selective settlement and habitatspecific differential post-settlement mortality, one would expect capture of settlement-size individuals in other habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Fish larvae have long been considered passive particles at the mercy of ocean currents, tides, and weather events (Montgomery et al, 2001). For reef Wshes, ecological evidence has demonstrated that passive dispersal alone cannot explain larval distributions (e.g., Leis and Carson-Ewart, 1998).…”
Section: Introductionmentioning
confidence: 99%